2011
DOI: 10.1186/1471-2105-12-370
|View full text |Cite
|
Sign up to set email alerts
|

Toponomics method for the automated quantification of membrane protein translocation

Abstract: BackgroundIntra-cellular and inter-cellular protein translocation can be observed by microscopic imaging of tissue sections prepared immunohistochemically. A manual densitometric analysis is time-consuming, subjective and error-prone. An automated quantification is faster, more reproducible, and should yield results comparable to manual evaluation. The automated method presented here was developed on rat liver tissue sections to study the translocation of bile salt transport proteins in hepatocytes. For valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…5). 38 Subsequent functional analysis in perfused rat liver revealed that CDC and its taurin‐ and glycin‐conjugates induce a significant reduction of net bile salt uptake within minutes (Fig. 5; Supporting Fig.…”
Section: Discussionmentioning
confidence: 97%
“…5). 38 Subsequent functional analysis in perfused rat liver revealed that CDC and its taurin‐ and glycin‐conjugates induce a significant reduction of net bile salt uptake within minutes (Fig. 5; Supporting Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Transporter retrieval from the plasma membrane was analyzed by assessing subcellular distribution of sinusoidal and canalicular transporters in immunofluorescence images from tissue sections of perfused rat liver by an automated image analysis method, as described previously [6,7]. Shortly, livers were perfused with 100 µmol/L of taurocholate (TC), taurochenodeoxycholate (TCDC) or control buffer for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…Expression pattern of cell markers can be manually counted from randomly selected visual microscopic fields, compared to total cell numbers (counted using nuclear counterstaining with DNA dye) and cell processes analysed. However, numbers of earlier studies have questioned reproducibility of manual evaluation of microscope images by trained experts, particularly when deciding between labelled and unlabelled cells . Thus, there is a need for automated and unbiased approaches for quantitative analysis in brain sections as well as in three‐dimensional brain architecture.…”
Section: Quantifying and Characterizing Cells In The Brainmentioning
confidence: 99%